Nutrition Analysis of Ciplukan Fruit as Nutritional Therapy for Hypertension - Permatasari, Rizqi Annisa; Kartikasari, Lilik Retna; Lestari, Anik (Global Health Science Group, 2024)
The prevalence of hypertension in the world increases every year. Hypertension is a non-communicable disease that occurs when systolic blood pressure exceeds 140 mm/Hg and diastolic blood pressure exceeds 90 mm/Hg. Oxidative stress is involved in the hypertension pathogenesis Objective: Ciplukan fruit (Physalis angulata L.) has beneficial health effect for hypertension patients. Ciplukan fruit has high mineral content and antioxidants, so it can help lower blood pressure. Therefore, the aim of this study was to analyze the nutritional contents of ciplukan fruit (CF). CF was obtained from Bandung West Java. Method: Minerals including potassium (K), calcium (Ca) and magnesium (Mg) levels were determined using the SSA-flame methods, whereas flavonoid and antioxidant activity were determined using spectrophotometry and DPPH. The evaluation was conducted at the Universitas Gadjah Mada (UGM) integrated research and testing laboratory (LPPT). Results: 100 g of CF contained 585 mg of potassium, 13 mg of calcium, 24 mg of Mg, 1,2% b/b of flavonoids, and 19,06 mg/ml antioxidant activity. Conclusions: CF is a good source of minerals and high antioxidant activity, which can be used as nutritional therapy for hypertension.